Fire risk assessment of heritage building – perspectives of regulatory authority, restorer and building stakeholder - Ibrahim, Md. Najib; Ibrahim, Mohd Shariffuddin; Mohd Din, Azrin; Abdul Hamid, Khirani; Mohd Yunus, Rodzyah; Yahya , Mohamad Ridzuan (2011)
This paper examines the perspectives of different parties involved in fire management/risks/protection system of heritage building. A survey questionnaire was developed based on the identified criteria of fire risks for heritage buildings in Malaysia. The survey questionnaire was administered to Fire Rescue Department Malaysia (FRDM) personnel, consultant and contractor, maintenance personnel (representing stakeholder). The data were analysed based on pair-wise comparison. It was found the perceptions of different parties differed from one another.